2013
DOI: 10.1002/syn.21673
|View full text |Cite
|
Sign up to set email alerts
|

Acute morphine associated alterations in the subcellular location of the AMPA-GluR1 receptor subunit in dendrites of neurons in the mouse central nucleus of the amygdala: Comparisons and contrasts with other glutamate receptor subunits

Abstract: Within the amygdala, AMPA receptors expressing the AMPA-GluR1 (GluR1) subunit play an important role in basal glutamate signaling as well as behaviors associated with exposure to drugs of abuse like opiates. Although the ultrastructural location of GluR1 is an important functional feature of this protein, the basal distribution of GluR1, as well as its sensitivity to acute morphine, has never been characterized in the mouse central nucleus of the amygdala (CeA). Electron microscopic immunocytochemistry employi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 62 publications
0
8
0
Order By: Relevance
“…This evidence suggests that increased glutamatergic activity in the CeA might underlie the central neural mechanisms of increased SNA and AP in response to ethanol administration. Combined with the fact that ethanol is able to cross the blood-brain barrier (48a), local CeA administration of glutamate could increase AP (27), and there is an abundant expression of NMDA receptors in the CeA (5,44,50,53), we hypothesized that the manifestation of cardiovascular and sympathetic responses to CeA injection of ethanol requires the activation of NMDA receptors expressed in CeA neurons in vivo. Consistent with this hypothesis, the present in vivo study found that sympathoexcitatory responses to CeA administration of ethanol were significantly attenuated by blockade of local NMDA receptors (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This evidence suggests that increased glutamatergic activity in the CeA might underlie the central neural mechanisms of increased SNA and AP in response to ethanol administration. Combined with the fact that ethanol is able to cross the blood-brain barrier (48a), local CeA administration of glutamate could increase AP (27), and there is an abundant expression of NMDA receptors in the CeA (5,44,50,53), we hypothesized that the manifestation of cardiovascular and sympathetic responses to CeA injection of ethanol requires the activation of NMDA receptors expressed in CeA neurons in vivo. Consistent with this hypothesis, the present in vivo study found that sympathoexcitatory responses to CeA administration of ethanol were significantly attenuated by blockade of local NMDA receptors (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the CeA is innervated by several excitatory transmitters (22, 50), but among the most prominent is L-glutamate. Not only does the CeA contain an abundance of glutamatergic nerve terminals (41), evidence also indicates that neurons in the CeA express ionotropic excitatory receptors: the ␣-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA) receptor and the N-methyl-D-aspartate (NMDA) receptor (5,43,49,51). Given the evidence that local CeA administration of glutamate increases AP (27) and alcohol consumption could activate NMDA receptors expressed in the CeA nucleus in vivo (40, 49), we further hypothesized that sympathoexcitatory and pressor responses evoked by CeA injection of ethanol may involve the activation of local NMDA receptors.…”
mentioning
confidence: 99%
“…Thus, an important mechanism for opioid-induced postsynaptic adaptations involves receptor internalization or downregulation on spines (46), and changes in density or composition of receptors at dendritic spines modulate synaptic output (75). For instance, ionotropic glutamate receptors on neurons in the central amygdala diffuse to dendritic compartments more proximal to the soma after noncontingent morphine administration, facilitating signal propagation (76). Such changes are expected to impact dendritic processing of glutamatergic and gamma-aminobutyric acidergic inputs.…”
Section: Receptor Composition and Densitymentioning
confidence: 99%
“…It was hypothesized that GluR1 and GluR2 transport may be one of the reasons of hyperalgesia caused by remifentanil [25]. Acute administration of morphine altered the subcellular distribution of AMPAR subunit (GluR1 and GluR2) in mouse neuronal dendrites [4]. After xylazine administration, the gene expression of GluR1 in the hippocampus significantly decreased in groups X3, X4, X5, and X6 when compared to group C. In addition, the protein expression was significantly decreased, but the changes in gene and protein expression of GluR2 were not significant.…”
Section: Discussionmentioning
confidence: 99%